Convergent Intelligence for Pandemic Preparedness: A Narrative Review of Integrated Digital Biosurveillance Systems Utilizing Pre-Diagnostic Data Streams - Alnassar, Khaloud Abdullah Fahad; Nora Yahya Hussain Humadi; Taleb Huraymis Almutairi; Amal Mohamad Almadani; Nooh Thawab Almotiri; Abdulrahman Ali Nasser Alharbi; Ahmed Mueibid Mohammed Alharbi; Abdulaziz Khalaf Ghareeb Aldhaferi; Ahmed Mohammed Osaykir Alrashdi; Fahad Nazal Khalaf Alalawi; et al. (Saudi Journal of Medicine and Public Health, 2024)
Background: The early detection of infectious disease outbreaks is a critical public health imperative. Traditional surveillance, reliant on confirmed laboratory reports, often introduces a critical delay. The concept of the biosurveillance continuum advocates for the real-time integration of pre-diagnostic data streams from across the healthcare ecosystem to provide earlier warning. Aim: This narrative review systematically synthesizes the literature on integrated systems that combine syndromic Emergency Medical Services (EMS) data, over-the-counter (OTC) pharmacy sales, radiology findings, and nursing home reports for the early detection of infectious disease outbreaks. Methods: A systematic search was conducted across PubMed/MEDLINE, CINAHL, Scopus, and IEEE Xplore for studies published between 2010-2024. A narrative synthesis was performed, analyzing system architectures, detection performance, and implementation challenges. Results: Each data stream offers unique benefits for public health monitoring. EMS data ensures geographic and temporal insight into illnesses like influenza-like illness (ILI). Over-the-counter (OTC) sales data reflect symptom onset across populations. NLP analysis of radiology reports can detect pneumonia cluster patterns before definitive diagnosis. Nursing home data provides vital surveillance for high-risk groups. Effective integration of these sources necessitates Health Informatics platforms for data aggregation and visualization, supported by robust epidemiological frameworks. Conclusion: An integrated biosurveillance system utilizing EMS, pharmacy, radiology, and nursing home data can improve early outbreak detection. However, challenges such as data standardization, interoperability, privacy, and collaboration must be addressed to maximize its effectiveness. Investing in these systems is crucial for pandemic preparedness.